The Right Non Self-Incrimination and Epistemology of Criminal Witnesses - Zahri Kurniawan; Ilham Wahyudi; H.S. Tisnanta (Universitas Lampung, 2020)
The absence of a clear normative interpretation related to witnesses who are also criminal perpetrators in the Indonesian court has controversy on the theoretical level. In practice, the practitioners adopt a concept known in other countries. However, in adopting ideas from other countries, practitioners are often trapped in practitioners’ paradigms. Translating the perpetrators’ witnesses such as crown witnesses, justice collaborators (JC), and whistleblowers (wb,) are not the concepts comprehensively. In the end, the witness being denied the rights of the perpetrators, namely right non-self-incrimination. The paper offers a concept for finding solutions in the use of witnesses who are also as criminal perpetrators in epistemological basis. These considerations are used to provide a coherent way based on the principle to justify the use of witness evidence from the criminal perpetrators. The purpose is to accord with the principle of due process of law, not to clash the principle of non-self-incrimination in proving the search of material truth.